On a new genus and four new species of the subfamily Cyprettinae (Crustacea, Ostracoda) from Brazilian floodplains - Ferreira, Vitor Góis; Higuti, Janet; Martens, Koen (Zootaxa, 2023)
We describe the new genus Triangocypretta gen. nov. and four new species from Brazilian floodplains. Triangocypretta angustus gen. et spec. nov. and Triangocypretta labiata gen. et spec. nov. were described from the Amazon floodplain only, while Triangocypretta nates gen. et spec. nov. was described from Amazon, Araguaia, and Paraná River floodplains. Triangocypretta hirsuta gen. et spec. nov. was recorded from all four floodplains: Amazon, Araguaia, Pantanal and Paraná. The new genus is characterized by the triangular shape of the carapace in lateral view, the absence of teeth on the posteroventral inner list in the right valve and the presence of anterior marginal septa in both valves, as well as by the relatively short and thin α and β-setae on the mandibular palp. All populations found were asexual. Owing to the clear differences in valve anatomy and limb chaetotaxy as compared to species of Cypretta s.s., the four species were allocated to a new genus in the subfamily Cyprettinae.